2020
DOI: 10.3390/molecules25215037
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide and Its 14-Aryloxy Analogues Inhibit Zika and Dengue Virus Infection

Abstract: Andrographolide is a labdene diterpenoid with potential applications against a number of viruses, including the mosquito-transmitted dengue virus (DENV). In this study, we evaluated the anti-viral activity of three 14-aryloxy analogues (ZAD-1 to ZAD-3) of andrographolide against Zika virus (ZIKV) and DENV. Interestingly, one analogue, ZAD-1, showed better activity against both ZIKV and DENV than the parental andrographolide. A two-dimension (2D) proteomic analysis of human A549 cells treated with ZAD-1 compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 52 publications
(77 reference statements)
0
24
0
Order By: Relevance
“…Likewise, other researchers have also shown the inhibitory and suppressive effects of AGL on viruses such as human immunodeficiency virus (HIV) [13], herpes simplex virus type 1(HSV-1) [13,14], hepatitis B (HBV) [15], hepatitis C (HCV) [16], and influenza virus [17]. Similarly, AGL was shown to be effective as an anti-viral agent against the Zika virus [18] and Chikungunya [19]. AGL has been used in large amounts to boost up immunity during viral outbreaks worldwide including the Indian dengue outbreak in 2006, where it was proved effective with a decrease in (+ve) cases and infection.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Likewise, other researchers have also shown the inhibitory and suppressive effects of AGL on viruses such as human immunodeficiency virus (HIV) [13], herpes simplex virus type 1(HSV-1) [13,14], hepatitis B (HBV) [15], hepatitis C (HCV) [16], and influenza virus [17]. Similarly, AGL was shown to be effective as an anti-viral agent against the Zika virus [18] and Chikungunya [19]. AGL has been used in large amounts to boost up immunity during viral outbreaks worldwide including the Indian dengue outbreak in 2006, where it was proved effective with a decrease in (+ve) cases and infection.…”
Section: Introductionmentioning
confidence: 92%
“…Similarly, Ramalingam et al [21] applied maximum nontoxic AGL dose and showed most of the antiviral inhibitory effects with DENV 1-4-infected Vero cells. Recently, Li et al [18] evaluated the anti-viral activity of AGL against the Zika (ZIKV) and Dengue (DENV) viruses and confirmed their potential to be developed as an anti-ZIKV, anti-DENV herbal agents. Moreover, Kaushik et al [22] used in vitro and in silico studies to characterize the isolated compounds from AGL with its active anti-dengue property against DENV-2.…”
Section: Introductionmentioning
confidence: 98%
“…To our eyes, these studies represent key research advances regarding the development of drugs for the control of ABD. Furthermore, recent reviews providing well-updated scenarios about drug development against selected ABD and formulating new research challenges are outlined [14][15][16][17][18][19][20][21][22][23]. Among key ABD, major focuses have been malaria, Chagas disease, dengue, human African trypanosomiasis (HAT), leishmaniasis, and Zika.…”
Section: The Editors' Pickmentioning
confidence: 99%
“…12,13 In general, preclinical studies have reported mostly antibacterial [14][15][16] and anti-inflammatory effects [17][18][19] for A. paniculata and its bioactive compounds. More recently, the antiviral properties of this plant as well as its phytoconstituent andrographolide have been increasingly investigated and reported for a wide array of viruses including dengue, 20,21 chikungunya, 22 zika, 23 and influenza. 24 Since the beginning of the pandemic in 2020, several narrative reviews have highlighted A. paniculata and andrographolide as potential antivirals in the treatment of COVID-19.…”
mentioning
confidence: 99%